2018
DOI: 10.1002/jmrs.273
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐containment in hypofractionated radiation therapy: a literature review

Abstract: Recent technological advances in radiation therapy have allowed for greater accuracy in planning and treatment delivery. The development of hypofractionated radiation treatment regimens is an example, and has the potential to decrease the cost per episode of care, relative to conventional treatments. Our aim was to analyse published literature on the cost‐effectiveness and budgetary implications of hypofractionated radiation therapy. As such, this article will quantify the projected health care cost savings an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 31 publications
1
35
0
2
Order By: Relevance
“…La diminution du taux de remplissage des appareils de traitement liée à l’hypofractionnement peut à terme poser aussi la question de l’évolution du besoin en manipulateurs. Bien qu’aujourd’hui en France, l’offre d’emploi des manipulateurs est inférieure à la demande, un questionnement sur les besoins en ressources humaines des services de radiothérapie est partagé par plusieurs auteurs notamment pour prévenir une offre excédentaire dans ce secteur [33] . À court terme, les créneaux libres des appareils de traitement pourraient être consacrés à des activités de recherche clinique, d’enseignement, et de formation continue du personnel y compris la mise en situation de simulation des événements indésirables (tels que des « chambre des erreurs ») [34] .…”
Section: Discussionunclassified
“…La diminution du taux de remplissage des appareils de traitement liée à l’hypofractionnement peut à terme poser aussi la question de l’évolution du besoin en manipulateurs. Bien qu’aujourd’hui en France, l’offre d’emploi des manipulateurs est inférieure à la demande, un questionnement sur les besoins en ressources humaines des services de radiothérapie est partagé par plusieurs auteurs notamment pour prévenir une offre excédentaire dans ce secteur [33] . À court terme, les créneaux libres des appareils de traitement pourraient être consacrés à des activités de recherche clinique, d’enseignement, et de formation continue du personnel y compris la mise en situation de simulation des événements indésirables (tels que des « chambre des erreurs ») [34] .…”
Section: Discussionunclassified
“…Under the current payment model, the cost of radiotherapy is based on the number treatments delivered. Although HFRT is reported to be more resource‐efficient and less costly compared with CFRT in patients with breast cancer and prostate cancer, to date no study has reported the economic value of preoperative HFRT in esophageal cancer. On comparing the time commitments and costs related to therapy, we found that preoperative HFRT can significantly shorten the durations of both radiotherapy and hospitalization (16.7 and 69.0 days, respectively) compared with CFRT (32.8 and 80.4 days, respectively) by requiring fewer fractions.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 However, the current payment system disincentivizes the use of shorter fractionation schemes and other highly cost-effective treatments, such as brachytherapy. [15][16][17][18] Value-based care is what patients deserve, and it is what we should strive to provide them. The existing fee-for-service system does not reliably incentivize delivery of the most cost-effective treatment.…”
Section: Shifts In Evidence-based Care and The Road Aheadmentioning
confidence: 99%
“…The new Medicare payment system ensures that practices not participating in APMs will have lower annual payment updates than those participating. Practices that avoid APMs will struggle, either financially through lower payment 19 or through additional burdens of quality reporting and prior authorization. ASTRO leaders have concluded that the best option moving forward for the specialty is an APM designed by and for radiation oncologists.…”
Section: Shifts In Evidence-based Care and The Road Aheadmentioning
confidence: 99%